The Role of Value Congruence and Inter Organizational Knowledge Sharing in Improving Relationship Quality in the Business Community - Adelia Ika Damayanti; Dita Prameswari (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2022)
Background: The direction and purpose of a business is to create the welfare of the people where the welfare of the people can be achieved by maintaining business continuity. One effort that can be done is to be affiliated or incorporated in a business community.   Purpose: The purpose of this study is to develop two concepts that determine Relationship Quality between members of the business community. The two concepts are Value Congruence and Inter Organizational Knowledge Sharing (IOKS).   Methods: The research method used is a literature survey to define concepts and develop measurements.   Conclusion: The results of the study found that Value Congruence can be defined as the level of value conformity between the company and the community that is followed in achieving goals, and is measured using relationship, security, and prestige. Meanwhile, Inter Organizational Knowledge Sharing is a company's willingness to share the knowledge they have acquired with other companies in the same community, which is measured by knowledge donating (sharing knowledge to other companies) and knowledge collecting (gathering knowledge from other companies). Both concepts are believed to improve the quality of relationships between members in the community.   Suggestion: Future research will be conducted to validate the definitions of concepts and measures that have been developed and to empirically test causality between concepts.